2020
DOI: 10.1128/aac.02213-19
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Methicillin-Resistant Staphylococcus aureus Nares Screening for Patients with a Diabetic Foot Infection

Abstract: Treatment of suspected methicillin-resistant Staphylococcus aureus (MRSA) is a cornerstone of severe diabetic foot infections; however, antibiotics can be associated with toxicity. The objective of this study was to determine the negative predictive value (NPV) of MRSA nares screening in the determination of subsequent MRSA in patients with a diabetic foot infection. This was a retrospective cohort study across Veterans Affairs (VA) medical centers from 1 January 2007 to 1 January 2018. Data from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Hand et al 13 found that the positive and negative predictive values of prior infection or colonization with MRSA for the subsequent recovery of MRSA were 54% and 97%, respectively. Mergenhagen et al 5 evaluated the utility of MRSA nares screening for patients with DFI. The NPV of MRSA nares screening for MRSA DFI was 89.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand et al 13 found that the positive and negative predictive values of prior infection or colonization with MRSA for the subsequent recovery of MRSA were 54% and 97%, respectively. Mergenhagen et al 5 evaluated the utility of MRSA nares screening for patients with DFI. The NPV of MRSA nares screening for MRSA DFI was 89.6%.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Current guidelines recommend selection of empiric antibiotics based on severity of infection, risk factors for or history of colonization or infection with methicillinresistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa, and local prevalence of these organisms. 3,4 Prior studies documented high rates of unnecessary empiric anti-MRSA and anti-pseudomonal therapy 5,6 based on correlation with microbiologic results; however, most of these studies excluded patients with negative or no microbiologic testing. In "real-world" settings, microbiologic testing may not be performed, or testing may be negative due to inadequate sampling, sampling after the initiation of antibiotics, or absence of true infection.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all 31 coagulase-positive S. aureus were susceptible to novobiocin and all 73 coagulase-negative S. aureus were susceptible to methicillin. An investigation by Mergenhagen et al (35) determined that the prevalence of Staphylococcus aureus isolated from patients with DFUIs was 89.2%, with 7.5% of MRSA and 24.8% of methicillinsusceptible Staphylococcus aureus. Recently, Anafo et al (36) investigated the variety of bacteria in 100 patients with DFUIs in Ghana and found that S. aureus was the most prevalent bacterium showing resistance to penicillin (100%), tetracycline (47.4%), cotrimoxazole (42.1%) and so on.…”
Section: Discussionmentioning
confidence: 99%
“…A common way to de-escalate empiric broad spectrum antibiotic therapy, especially for respiratory and diabetic foot infections, is through a polymerase chain reaction nares test for methicillin resistant Staphylococcus aureus , which can lead to early discontinuation of vancomycin when negative. 11,12 Another effective de-escalation method is switching from IV to oral administration of antibiotics, when appropriate. Overall, the efforts of antimicrobial stewardship that have been wildly utilized indeed parallel the goals of fluid stewardship.…”
Section: Discussionmentioning
confidence: 99%